Chapter 10 Conclusion, Discussion and Recommendations - Marian Thunnissen; Paul Boselie (Emerald Publishing Limited, 2024)
This final chapter of this book highlights and critically discusses some specific issues concerning talent management in the context of higher education raised in the chapters of this book. It recapitulates the transition higher education is going through. This transition started decades ago but was boosted by the movements of Open Science and Recognition and Rewards. It leads to a reorientation on the conceptualization of academic performance and subsequently also on the meaning of talent and talent management in academia. It points to a shift from an exclusive and performance orientation on talent, to an inclusive, developmental approach to talent management or a hybrid form. Yet, Thunnissen and Boselie state that there is a talent crisis in academia, and this crisis urges the need for more innovative ways of developing and implementing talent management practices. This chapter ends with some recommendations for further talent management research and practice.
10.1108/978-1-80262-685-820241010; 10.1108/978-1-80262-685-820241010; Talent Management in Higher Education; EBP10429552X